(untitled) (Journal of the College of Education for Women, 2019)
Witnessing human societies with the turn of the century atheist twenty huge revolution in information , the result of scientific and technological developments rapidly in space science and communications , and that made the whole world is like a small village not linked by road as it was in ancient times, through the rapid transportation as was the case a few years ago , thanks to the remote sensing devices that roam in space observant everything on the ground , that the information networks that overflowed the world a tremendous amount of information provided for each inhabitants of the earth , which made this information requirement for human life and human survival and well-being , as it has allowed that information to humans opportunity in the management of many of the phenomena geographical Ptoukaha and directed to serve the community and well-being.This innovation, which was called at that time as " computer " , who had infiltrated the computer to all domains and scientific applications and advanced to the games and entertainment and accounting software and business management to multimedia. Geography was not outside the scope of the computer , where I consider many of the workers in the field of decision-making geographical urban planners and managers of natural resources that the potential of the computer is the right tool to accommodate the potential of computing platforms and geographical quantity together . Within this framework, promising to call later GIS "Geographic Information System GIS".